(Invited) High Efficiency Green-Yellow Emission from InGaN/GaN Quantum Well Structures Grown on Overgrown Semi-Polar (11-22) GaN on Regularly Arrayed Micro-Rod Templates. (13th April 2015) - Gong, Y; Xing, K; Xu, B; Yu, X; Li, Z; Bai, J; Wang, Tao
Abstract : A simple but cost-effective overgrowth technique has been developed for the growth of semi-polar (11-22) GaN on mask-patterned micro-rod array templates fabricated on thin (11-22) GaN layers on sapphire. As a result, a fast coalescence with a thickness of 1 μm has been obtained. Massively improved crystalline quality has been achieved, confirmed by detailed X-ray rocking curve measurements, which show that the full width at half maximum (FWHM) has been reduced to 0.096° and 0.097° at both 0° and 90° azimuth angle measured on an overgrown sample with a total thickness of 4.5 μm. The root mean square (RMS) roughness measured by atomic force microscopy is 1.47 nm. A number of InGaN/GaN multiple quantum well (MQW) structures with high In composition have been grown on the overgrown semi-polar GaN templates, showing strong photoluminescence (PL) emission with a wavelength from 495 to 590 nm at room temperature. Temperature dependent PL measurements have been performed to estimate their internal quantum efficiency (IQE), demonstrating 8% of IQE for the sample with an emission wavelength of 590 nm. Power dependent PL measurements indicate weak quantum confined Stark effects (QCSE).